Association between intrahepatic triglyceride content in subjects with metabolically healthy abdominal obesity and risks of pre-diabetes plus diabetes: an observational study. Issue 2 (21st February 2022) - Xu, Qiaoyan; Zhang, Junfeng; Han, Haiwei; Chen, Ning; Lai, Fangfang; Liu, Yongwen; Huang, Caoxin; Lin, Mingzhu; Zhang, Wei; Wang, Shunqin; Liu, Changqin; Li, Zhibin
Abstract : Objective: We aimed to evaluate the association of intrahepatic triglyceride (IHTG) content in subjects with metabolically healthy abdominal obesity (MHAO) on risks of pre-diabetes plus diabetes. Design: Cross-sectional survey. Setting: Lianqian community, the First Affiliated Hospital of Xiamen University, Xiamen, China. Participants: Among 1523 community-living healthy adults aged 40 years or older with abdominal obesity recruited at baseline, 428 subjects who underwent IHTG content measurement were selected. Outcome measures: Risk of pre-diabetes plus diabetes. Results: Non-alcoholic fatty liver disease (NAFLD) was diagnosed as 203 (69.1%) in MHAO and 121 (90.3%) in metabolically unhealthy abdominal obesity (MUAO) (p<0.001). The prevalence rates of pre-diabetes plus diabetes were 81.1%, 88.8% and 90.9% across the tertiles of IHTG content (p=0.037). Both MUAO (vs MHAO) and NAFLD (vs non-NAFLD) were independently associated with increased risks of pre-diabetes plus diabetes, the adjusted ORs (95% CIs) were 10.90 (3.15 to 37.69, p<0.001) and 3.02 (1.47 to 6.20, p=0.003), respectively. Higher IHTG content was significantly associated with increased risk of pre-diabetes plus diabetes with the adjusted OR (95% CI) of per SD increase of IHTG content of 1.62 (1.07 to 2.46, p=0.024). And there was a significantly positive trend between increasing categories of IHTG content tertiles and excessive risks of pre-diabetes plus diabetes (trend test p value=0.011). Stratified analyses showed similar results on the associations of NAFLD and IHTG content with risks of pre-diabetes plus diabetes for subjects with MHAO but not for those with MUAO. Conclusions: NAFLD and higher IHTG content were independently associated with increased risks of pre-diabetes plus diabetes in MHAO subjects. NAFLD or quantity of liver fat should be considered as additional criterion when defining and diagnosing MHO. Screening of NAFLD and intervention to reduce liver fat should be strengthened even for those seemly metabolically healthy obese.